(untitled) (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Definition of chronic renal disease is based on the presence of kidney damage or glomerular filtration rate (GFR 60 ml/min per 1.73 m2) for 3 months, irrespective of cause. Once they are diagnosed as CKD, they are kept either on hemodialysis or peritoneal dialysis or patient undergo renal transplant. With this research we may prove that even in a similar circumstances failure rate of AVF is more in diabetes patient. Methods: Total 50 patients of either gender were taken in this study. Inclusion criteria: CRF with GFR <30ml/min. Arterial diameter >1.5mm and venous diameter >2mm. Preoperative radial artery blood flow >30cm/min. Exclusion criteria: arterial diameter <1.5mm venous diameter <2mm. Written consent was taken from the patient. After preoperative workup surgery was done by 1st author. Arterio-venous fistula was scanned by color Doppler imaging after 4 weeks. Result: There were 31 [62%] male, 19 [38%] female. Mean age of patients was 55.8 years. 18(36%) were dialysis dependent. Cause of renal failure were diabetes 16(32%), unknown 15(30%), glomerulonephritis 8(16%) and obstructive uropathy 3(6%). Mean internal diameter of radial artery was 1.91mm (1.5-2.6) and cephalic vein 2.57mm (1.9-3.2). 7 patients had swelling of arm, 5 patients has surgical site infections and 15 patients had primary failure; 11 were from diabetic group and 4 from non-diabetic group. Mean duration of surgery was 60.95 minutes (50-75). Average preoperative velocity in radial artery was 32.94(30-39) cm/sec. Average flow of blood at the end of 4 weeks was 461.42ml/min (0-654). Between two groups failure rate was significantly high in diabetic patients (p = 0.02). Failure rate was significantly higher in patients with diabetes more than 10 years (p=0.01). Conclusion: Failure rate of arterio-venous fistula is significantly high in diabetic patients.